Peran Pengembangan Ekonomi Kreatif dalam Meningkatkan Daya Saing UMKM di Indonesia - Solagratia Raya Manalu; Rosianna Dorepa Gultom; Maynisa Naomi Marpaung; Putri Alechia Simbolon (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy. However, globalization and digital transformation require MSMEs to continuously improve their competitiveness. One strategy that can be implemented is the development of the creative economy, which emphasizes innovation, creativity, and technology utilization. This study aims to analyze the role of creative economy development in enhancing the competitiveness of MSMEs in Indonesia. The research employs a literature review method by examining relevant journals, books, and reports. The findings indicate that the creative economy contributes to product quality improvement, business innovation, market expansion, and brand strengthening. Furthermore, digital technology utilization enhances business efficiency and productivity. Therefore, creative economy development can serve as an effective strategy to strengthen the competitiveness of MSMEs in Indonesia.